Quantum-resilient software security: A fuzzy AHP-based assessment framework in the era of quantum computing. - Sultan H Almotiri (PLoS ONE)
The introduction of quantum computing has transformed the setting of information technology, bringing both unprecedented opportunities and significant challenges. As quantum technologies continue to evolve, addressing their implications for software security has become an essential area of research. This paradigm change provides an unprecedented chance to strengthen software security from the start, presenting a plethora of novel alternatives. We use a multi-criteria decision-making methodology in this work to evaluate the efficacy of quantum computing approaches in improving software security. As the number of electronic applications grows, software developers strive to produce more sophisticated and user-friendly alternatives. However, in the pursuit of complexity, vulnerabilities may be introduced inadvertently, posing a substantial danger to software security. Our study addresses five major components of the quantum method to overcome these challenges: lattice-based cryptography, fully homomorphic algorithms, quantum key distribution, quantum hash functions, and blind quantum algorithms. The rapid development of quantum bits (qubits) regarded as basic quantum entities adds complexity and risk to the software security landscape. As a result, in the age of quantum computing, evaluating software security becomes not only necessary but also critical. To accomplish this objective, we propose the Fuzzy Analytic Hierarchy Process (F-AHP), a soft computing method, as a reliable tool for accomplishing this goal. Our research aims to prioritise security variables using quantum security criteria, providing an innovative viewpoint on software security evaluation in the quantum computing era.